SARAH DRY, The Newton Papers: The Strange and True Odyssey of Isaac Newton’s Manuscripts - Yeo, Geoffrey (Archivaria, 2015)
The Newton Papers: The Strange and True Odyssey of Isaac Newton’s Manuscripts. SARAH DRY. New York: Oxford University Press, 2014. xi, 238 pp. ISBN 978-0-19-995104-8.